THE EFFECT OF BRAND EQUITY AND CELEBRITY ENDORSER TO PURCHASE INTENTION ON MAYBELLINE PRODUCTS MODERATED BY PRODUCT QUALITY - Gabriella Angel; Nurhadi Nurhadi (STKIP Singkawang, 2023)
This study aims to determine the effect of Brand Equity, and Celebrity Endorser on Purchase intention of Maybelline products moderated by Product Quality. This consists of variables Brand Equity (X1), Celebrity Endorser (X2), Product Quality (Z), and Purchase Intention (Y). To obtain data using questionnaires distributed through random sampling technique with a sample of 100 respondents. The analysis uses multiple linear regression with Moderated Regression Analysis which is processed using the SPSS application. The results prove that simultaneously all variables have a positive and significant effect on Purchase Intention. While partially, Brand Equtiy and Celebrity Endorser have a positive and significant effect on Purchase Intention of Maybelline, and the position of Product Quality does not have the potential to be an independent variable but as a pure moderating variable. The results of the MRA test prove that product quality does not moderate the effect of brand equity on Purchase Intention, but moderates the influence of celebrity endorsers on Purchase Intention